2014
DOI: 10.1063/1.4895909
|View full text |Cite
|
Sign up to set email alerts
|

Anti-liquefaction characteristics of composite bucket foundations for offshore wind turbines

Abstract: Occurrence of liquefaction in saturated sandy deposits under structure foundation can cause a wide range of structural damages from minor settlement to general failure because of bearing capacity loss. By comparing traditional foundations for offshore wind turbines, the soil inside and underneath the composite bucket foundation is subjected to the overburden pressure from the foundation self-weight and constrained by a half-closed bucket skirt. The objective of this paper is to clarify the effects of the soil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…To meet the various marine engineering challenges in the future and improve the liquefaction-resistant performance of the foundations, many innovative structure improvements have been proposed (Table 2). [64,68], large-scale prestressed concrete bucket foundation [76,77], tripod suction bucket foundations [78], modified suction caisson with external skirt [79,80], modified suction buckets with honeycomb compartment [81] Floating Deep water (>50 m)…”
Section: Foundation-supported Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet the various marine engineering challenges in the future and improve the liquefaction-resistant performance of the foundations, many innovative structure improvements have been proposed (Table 2). [64,68], large-scale prestressed concrete bucket foundation [76,77], tripod suction bucket foundations [78], modified suction caisson with external skirt [79,80], modified suction buckets with honeycomb compartment [81] Floating Deep water (>50 m)…”
Section: Foundation-supported Structuresmentioning
confidence: 99%
“…According to the detailed geological surveys and the seismic fortification intensity of this site (7 degrees), Zhang et al used the ADINA program to analyze the liquefaction-resistance ability of soils below and inside this foundation and showed improvements due to the overburden pressure of the foundation and the constraint effect of the skirt [76,77]. They found that the concrete bucket foundation could still work after soil liquefaction.…”
Section: An Example On Sitementioning
confidence: 99%
“…A three-dimensional finite-element model for a suction bucket foundation was presented by [136], whereas [137] presented a three-dimensional limit method for the stability analysis of suction buckets. The modelling of gravity-based and suction bucket foundations still require the definition of an applicable dynamic stiffness, accounting for cyclic degradation and liquefaction [138,139]. An increasing popularity of these alternative foundation concepts may instigate the need for industry-standard force-response relations as well.…”
Section: Soil-structure Interactionmentioning
confidence: 99%
“…Many experimental and numerical studies have been conducted on offshore wind turbines, such as the monopile [4], jacket support structure [5], tripod [6], and floating offshore wind turbines [7]. In recent years, a large number of offshore windfarms have already been installed, are under construction, or are being planned in China [8], and a new kind of suction foundation called composite bucket foundation for offshore wind turbines was proposed by Tianjin University [9][10][11][12]. The composite bucket foundation takes full advantage of the high tensile capacity of the steel strand and the high compressive capacity of the concrete.…”
Section: Introductionmentioning
confidence: 99%